The H-reflex modulation in lying and standing positions in young canoeists - Mazur-Różycka Joanna; Gajewski Jan; Buśko Krzysztof; Michalski Radosław; Łach Patrycja (Sciendo, 2014)
Study aim: to evaluate the differences in H-reflex parameters in lying and standing positions in canoeists.